Thinking skills for secondary school students in Malaysia - Kiong, Tee Tze; Yunos, Jailani Md; Heong, Yee Mei; Hj. Hussein, Atan; Mohamad, Mimi Mohaffyza (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The purpose of this research was to identify the level of higher order thinking skills among lower secondary students in Malaysia. A higher order thinking skills test was modified and distributed to 384 students throughout the whole country to assess their higher order thinking skills levels. The results showed that higher order thinking skills levels among the students were at very low level. The findings also revealed that there was a low positive significant relationship between the higher order thinking skills and academic result, r = 0.468, p < 0.05. In addition, the results indicated that there was a significant difference in Living Skills subject results on the higher order thinking skills. The authors proposed a new approach by using a specialised instructional module for individualised learning to deliver the thinking skills learning task.